2014
DOI: 10.1186/1471-2164-15-601
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence analysis reveals differences in population management and selection of European low-input pig breeds

Abstract: BackgroundA major concern in conservation genetics is to maintain the genetic diversity of populations. Genetic variation in livestock species is threatened by the progressive marginalisation of local breeds in benefit of high-output pigs worldwide. We used high-density SNP and re-sequencing data to assess genetic diversity of local pig breeds from Europe. In addition, we re-sequenced pigs from commercial breeds to identify potential candidate mutations responsible for phenotypic divergence among these groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 55 publications
2
63
1
Order By: Relevance
“…Their use is also becoming feasible because of the lower genotyping costs, for example, of the Porcine SNP60 Bead-array (Ramos et al, 2009) that has recently been used for comparative studies between European pig breeds (Manunza et al, 2013;BurgosPaz et al, 2013;Herrero-Medrano et al, 2014). However, there is a well-known ascertainment bias implicit when SNP chips are used in cattle and other livestock species (Albrechtsen et al, 2010;Lachance and Tishkoff, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their use is also becoming feasible because of the lower genotyping costs, for example, of the Porcine SNP60 Bead-array (Ramos et al, 2009) that has recently been used for comparative studies between European pig breeds (Manunza et al, 2013;BurgosPaz et al, 2013;Herrero-Medrano et al, 2014). However, there is a well-known ascertainment bias implicit when SNP chips are used in cattle and other livestock species (Albrechtsen et al, 2010;Lachance and Tishkoff, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Herrero‐Medrano et al. () suggested that European local pig breeds have exceptionally high levels of both ROHs and potentially damaging mutations, probably a combination of their European heritage and current low effective population size.…”
Section: The Domestication Bottleneckmentioning
confidence: 99%
“…A popular approach to identify harmful mutations that are (almost) lethal is to screen populations for the absence of specific variants in homozygous state. If populations contain heterozygous carriers of such variants, homozygotes would be expected based on allele frequencies and carrier-carrier matings (Derks et al, 2017;Pausch et al, 2015;VanRaden, Olson, Null, & Hutchison, 2011). This method relies on the biological implications of the lethality of a variant-resulting in an absence of the allele in F I G U R E 1 Genomic consequences of inbreeding.…”
Section: Identification Of Deleterious Allelesmentioning
confidence: 99%
See 1 more Smart Citation
“…Every day the need for the use of molecular markers is becoming more evident, whether it is to help in assisted breeding programs or genetic analyses and the determination of population inbreeding (Herrero-Medrano et al, 2014;Schiavo et al, 2016;Peripolli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%